Social-Emotional Learning Training to Strengthen Emotional Regulation among Adolescents: Pelatihan Social-Emotional Learning untuk Memperkuat Regulasi Emosi Remaja - Ima Fitri Sholichah; Nadhirotul Laily; Desy Wulandari; Lusyana Amanda (Room of Civil Society Development, 2026)
Adolescence is marked by biological, cognitive, social, and emotional changes that require adaptive emotional regulation skills. This community service program aimed to introduce emotional regulation concepts and initial practices to adolescents through Social-Emotional Learning (SEL) training focused on self-awareness and self-management. The program was conducted at a school in Cerme Lor Village, Gresik, and involved 100 senior high school students. Activities included material presentation, group discussions, identification of emotional triggers, breathing exercises, butterfly hug, simple relaxation, and the development of personal action plans. Evaluation was conducted descriptively through facilitator observations, participant reflections, and reviews of the personal action plans. All registered participants attended the program until completion, engaged in discussions and practical activities, and completed personal action plans containing emotional triggers, selected regulation strategies, and implementation plans. However, the program did not employ a pretest–posttest design, a validated emotional regulation instrument, or follow-up assessment. Therefore, the findings describe program implementation and participant engagement rather than evidence of improved emotional regulation skills. Future programs should include pre- and post-intervention assessments and periodic follow-up evaluations.